MicroRNA expression profiling in peripheral blood mononuclear cells and serum of type 2 diabetic, pre-diabetic and normo-glycaemic individuals - Dias, Stephanie (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.